Tourists’ Motivations to Choose Indonesia as a Vacation Destination - HENDIJANI, Roozbeh BABOLIAN (Journal of Environmental Management and Tourism; Vol 9 No 4 (2018): JEMT Volume IX Issue 4(28) Summer 2018, 2018)
Purpose - It is pertinent for the government and tourism marketers of particular destinations to have a better understanding of tourists’ motivations to choose a destination. Since there is little academic knowledge in the tourism industry in Indonesia, this study explores the factors which motivate international tourists to select Indonesia as a vacation destination.  Design – Besides the theoretical implication of this research regarding tourism industry in Indonesia, this study also gives practical application into the matter of tourism industry in Indonesia. Methodology - Self-administrated questionnaires consisting of three sections were distributed randomly to 400 international tourists at the Jakarta International Airport (Soekarno-Hatta) and some popular tourist areas around Jakarta. Data collection was conducted from June to September 2016. Related analyses such as a multivariate analysis and a descriptive analysis were used to answer the objectives of this research. Findings - The findings show the motivations underlying choosing Indonesia for a vacation spot and why these factors should be considered by the Indonesian government and tourism marketers in developing marketing strategies. Originality - This article is one of the limited researches regarding tourism industry in Indonesia and definitely one of the few which discussing about the motivations of international tourists to that destination.